Pengaruh Kualitas SDM dan Motivasi Kerja terhadap Kinerja Karyawan Melalui Teamwork Sebagai Variabel Mediasi Pada PT. PLN UP3 (Persero) ULP Rivai - Alfiki, Rozi; Syarif, Amirudin; Heriyanto, Heriyanto (CV. ITTC INDONESIA, 2024)
This study examined the effect of human resource quality and work motivation on employee performance by adding teamwork as a mediating variable at PT PLN UP3 (Persero) Palembang ULP Rivai, and this study used a quantitative descriptive method. The location of the research object is PT PLN UP3 (Persero) Palembang ULP Rivai. as a source of primary and secondary data. The population was 123 people. The non-probability sampling technique was used with 95 PT PLN UP3 (Persero) Palembang ULP Rivai employees. The data collection methods used are literature study, interviews, and questionnaires. The data analysis technique used is software SmartPLS version 3 with outer model and inner model measurement methods. The results of this study are as follows: 1) The effect of HR quality on employee performance is positive but not significant, with a P-value of 0.395. 2) The effect of work motivation on employee performance is positive and significant, with a P-value of 0.040. 3) The effect of teamwork on employee performance is positive but insignificant P- value of 0.818. 4) The effect of teamwork on employee performance is positive but insignificant. with a P-value of 0.816. 5) The effect of work motivation on employee performance with teamwork mediation is positive but insignificant, with a P-value of 0.854.